2011
DOI: 10.1007/s10948-010-1123-z
|View full text |Cite
|
Sign up to set email alerts
|

Single Crystal Growth and Effect of Doping on Structural, Transport and Magnetic Properties of A1−x K x Fe2As2 (A = Ba, Sr)

Abstract: We demonstrate the preparation of large, free standing iron pnictide single crystals with a size up to 20 x 10 x 1 mm 3 using solvents in zirconia crucibles under argon atmosphere. Transport and magnetic properties are investigated to study the effect of potassium doping on the structural and superconducting property of the compounds. The spin density wave (SDW) anomaly at T s ~138 K in BaFe 2 As 2 single crystals from self-flux shifts to T s ~85 K due to Sn solvent growth. We show direct evidence for an incor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 28 publications
(48 reference statements)
3
26
0
Order By: Relevance
“…1) and SrFe 2 As 2 (Ref. 52), respectively. BaFe 2 As 2 single crystals were grown from Asrich self-flux in a glassy carbon crucible using prereacted FeAs 2 powders mixed with Ba and As.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…1) and SrFe 2 As 2 (Ref. 52), respectively. BaFe 2 As 2 single crystals were grown from Asrich self-flux in a glassy carbon crucible using prereacted FeAs 2 powders mixed with Ba and As.…”
Section: Methodsmentioning
confidence: 98%
“…52 From dc resistivity and magnetization measurements we obtained the Néel temperatures T N = 150 and 200 K for CaFe 2 As 2 (see Fig. 1) and SrFe 2 As 2 (Ref.…”
Section: Methodsmentioning
confidence: 99%
“…At about the same time, the first single crystals ( $ 3 Â 3 Â 0:2 mm 3 ) of the 122 superconducting compound Ba 1Àx K x Fe 2 As 2 were grown using Sn flux (Ni et al, 2008a), with an incorporation of $1% Sn [see Su et al (2009) for a report of up to 5% Sn] into the crystals, not just as inclusions but at least partly into the lattice as an impurity. It was clear in the Ni et al work that Sn from the metal flux had an important influence on the properties of crystals of the parent compound, BaFe 2 As 2 , depressing T S =T SDW from the known polycrystalline value of 140 to 85 K. The Sn incorporated in Ba 1Àx K x Fe 2 As 2 also affects the low-energy spin fluctuations in the NMR measurements (Baek et al, 2008;Sun et al, 2011) and causes a large upturn in the low temperature specific heat divided by temperature C=T . Rb doped BaFe 2 As 2 crystals grown in Sn flux have as much as 9% Sn included .…”
Section: Development Of Fluxes and Progress In Crystal Growingmentioning
confidence: 99%
“…Initial attempts to grow single crystals of pristine Ba122 and its superconducting variants were made employing the high temperature solution growth techniques using Tin as a flux agent. It was shown that approximately 1 at% of Sn from the flux is incorporated in the structure leaving detrimental effects on the physical properties of the grown crystals [16,17]. For example, the combined structural/magnetic transition in the Sn-grown Ba122 crystals was found to occur at temperatures close to 80 K, which is very different from a value of T $130 K for a polycrystalline sample [18].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, at the end of the growth experiment, single crystals should be removed mechanically from a solidified flux-matrix [19]. Since these crystals grow in the form of thin layers; exfoliation or even buckling of single crystalline platelets may occur due to stress used in the mechanical extraction [16,19]. Further, strain induced superconductivity in pristine '122' compounds has also been reported [21].…”
Section: Introductionmentioning
confidence: 99%